Development of blend PEG-PES/NMP-DMF mixed matrix membrane for CO2/N2 separation - Ashvin Viknesh Mahenthiran (14024822) (2022)
The carbon dioxide (CO2) separation technology has become a focus recently, and a developed example is the membrane technology. It is an alternative form of enhanced gas separation performance above the Robeson upper bound line resulting in the idea of mixed matrix membranes (MMMs). With attention given to membrane technologies, the MMMs were fabricated to have the most desirable gas separation performance. In this work, blend MMMs were synthesised by using two polymers, namely, poly(ether sulfone) (PES) and poly (ethylene glycol) (PEG). These polymers were dissolved in blend N-methyl-2-pyrrolidone (NMP) and dimethylformamide (DMF) solvents with the functionalised multi-walled carbon nanotubes (MWCNTs-F) fillers by using the mixing solution method. The embedding of the pristine MWCNTs and MWCNTs-F within the new synthesised MMM was then studied towards CO2/N2 separation. In addition, the optimisation of the loading of MWCNTs-F for blend MMM for CO2/N2 separation was also studied. The experimental results showed that the functionalised MWCNTs (MWCNTs-F) were a better choice at enhancing gas separation compared to the pristine MWCNTs (MWCNTs-P). Additionally, the effects of MWCNTs-F at loadings 0.01 to 0.05% were studied along with the polymer compositions for PES:PEG of 10:20, 20:20 and 30:10. Both these parameters of study affect the manner of gas separation performance in the blend MMMs. Overall, the best performing membrane showed a selectivity value of 1.01 + 0.05 for a blend MMM (MMM-0.03F) fabricated with 20 wt% of PES, 20 wt% of PEG and 0.03 wt% of MWCNTs-F. The MMM-0.03F was able to withstand a pressure of 2 bar, illustrating its mechanical strength and ability to be used in the post combustion carbon capture application industries where the flue gas pressure is at 1.01 bar. Other Information Published in: Environmental Science and Pollution Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11356-022-20168-3